(untitled) (Fiep Bulletin - online, 2012)
Part of this document has been recorded by Edgar Zeballos Burgoa, Delegate General of FIEP(International Federation of Physical Education) Bolivia from 1992 to 2006. Unfortunately, in previous FIEPBolivia administrations, few activities were carried out and the FIEP goals were not properly promoted in Bolivia. First Delegates. It is known that previous FIEP Delegates in Bolivia were Professor Emilio SotomayorLedezma (1974), Guido Ferrufino de La Paz and José Nuñez Ruiz de Cochabamba, and they have alwayswanted to integrate teachers with the teachers associations, but due to lack of economic resources and littleinterest from the teachers union, they never got to strengthen a homogeneous group, carrying out some trainingcourses restricted to the regions and areas specifically oriented to physical education classes at school.